Evaluacion del conocimiento de los estudiantes de la Universidad Antonio Nariño de la facultad de odontologia sobre la nueva clasificacion de las enfermedades periodontales. - AGUILAR AGUDELO, YELIZ ALEXANDRA; SABOGAL, HERRERA NATALIA (Universidad Antonio Nariño, 2024)
Periodontal conditions group a set of oral pathologies that develop at the gingival level and directly affect the tooth support structures, which have a variable etiology, mainly triggered by the location and accumulation of multiple bacteria from dental plaque. However, the development of periodontal disease is not only associated with the biofilm of bacterial plaque.